Place-Based Learning (PBL) and the use of everyday experience: review of a didactic proposal for fieldwork to learn Geography - Retana Quirós, Daniela (2023)
With the purpose of strengthening the development of geographic skills in students, the design and application of the strategy "Active Pause: Let's read the space!" follow the guide of the Place-Based Learning (PBL) theory. The strategy proposes to validate the relationships that the students have built with their immediate environment and transfer them to the academic learning scenario, thus recognizing an opportunity to evaluate the understanding of the curricular contents reviewed during the class and to position the students as agents of construction and transformation of their territoriality. The proposal identified a student role that make them active and necessary, and a teaching role of guidance and accompaniment, where formative evaluation takes special prominence in a scenario of undeniable curricular flexibility, understanding that spatial readings are made from the autonomy and immediate experience of the students.